2020
DOI: 10.1002/bse.2567
|View full text |Cite
|
Sign up to set email alerts
|

Relating the role of green self‐concepts and identity on green purchasing behaviour: An empirical analysis

Abstract: At present, consumers in emerging economies are becoming more conscious about environmental well-being. Therefore, organizations compete to make their products and practices more eco-friendly. Several studies have tried to explain the relationship between green consumerism and an individual's buying behaviour using traditional theories. However, there is quite a challenge in understanding the influence of green self-concept (GSC) and green self-identity (GSI) in predicting the green purchase intention (GPI) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 100 publications
2
62
1
1
Order By: Relevance
“…Similar to this finding, Fang and Lee [49] argued that consumers who are more concerned with the quality of food termed as "adventurous consumers", have higher intentions towards green consumption. This finding is also in line with the previous studies which mentioned that green self-concept [54] and subjective knowledge on environmental issues [55] positively correlate with green purchase intention.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to this finding, Fang and Lee [49] argued that consumers who are more concerned with the quality of food termed as "adventurous consumers", have higher intentions towards green consumption. This finding is also in line with the previous studies which mentioned that green self-concept [54] and subjective knowledge on environmental issues [55] positively correlate with green purchase intention.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, studies have shown that environmental self-identity is closely related to a series of environmental behavior indicators, including product selection and judgment of environmental dilemmas (Van der Werff et al, 2014). Another study defined the self-identity measure within the context of green consumers, which correlates with individuals' sensitivity to being associated with "green issues" (Carfora et al, 2017), and a consumer with a higher self-concept of personality will be addicted to green buying behavior (Sharma et al, 2020). In addition, based on the theoretical argumentation of the role identity perspective (Burke, 1991) and research findings from Hobman and Frederiks (2014), green role identity can be viewed as an individual's identification of him or herself as an environmentally-friendly person.…”
Section: Employees' Green Role Identity As a Mediatormentioning
confidence: 99%
“… 68 Personal traits of consumers are essential characteristics, which have a strong influence to shape the behavior of an individual to take action to accept unfamiliar genetically modified food products. In addition, Grebitus, Steiner and Veeman 69 identify the role of individuals personality in shaping the consumers’ willingness to accept GM food, which is a new gene technological product.…”
Section: Moderation Effect Of Food Technology Neophobiamentioning
confidence: 99%